UNSUR INTRALINGUAL DAN EKSTRALINGUAL SEBAGAI PENANDA DAYA BAHASA DAN NILAI RASA BAHASA DALAM KESANTUNAN BERKOMUNIKASI - Pranowo, Pranowo (Sunan Kalijaga State Islamic University Yogyakarta, 2015)
This study aims to describe the formal elements of extra-lingual and intra-lingual and power of language and the language politeness. This study uses the pragma-semantic theory. Source of data of this research are several private television programs (Indonesia Lawyer Club, Sentilan-Sentilun), Tempo Magazine (Catatan Pinggir ), and the caricature of Sindo Newspaper. The data are in the form of speeches and sentences, which contain extra-lingual and intra-lingual elements. The data analysis is performed by inventorying, classifying, identifying, and interpreting the data, based on the Pragma-semantic theory. The results are (1) forms of extra-lingual and intra-lingual elements are able to bring the power of language as power of criticism, the power of information, the power of banter, power of commands, and allure, (2) forms of extra-lingual and intra-lingual elements are able to bring the values of language, such as pleasure values, the respect values, and the happiness values.